THE DOCTRINE OF “SURVIVAL OF THE FITTEST” IN THE CALL OF THE WILD AND WHITE FANG BY JACK LONDON = HỌC THUYẾT “MẠNH ĐƯỢC YẾU THUA” TRONG TIẾNG GỌI NƠI HOANG DÃ VÀ NANH TRẮNG CỦA JACK LONDON - Nguyễn, Thị Hồng Nhung (2020)
The Call of the Wild and White Fang are world famous animal stories. Their author – Jack London succeeded in evoking the harsh nature, red in tooth and claw, in which the dogs in both stories – Buck and White Fang undergo cruelty by humans and rival dogs. Yet both fight ferociously and evolve in the life-and-death battles to gain mastery over their rivals and also, to be the last survivor. With the aim of shedding the light on how the doctrine of ‘Survival of the Fittest’ by Darwin is portrayed in London’s works, the writer adopts the qualitative research method, moving from the theoritical background to in-depth analysis of two works. Gradually, the reader can see how Buck and White Fang take advantage of their strength, courage and intelligence to survive fierce struggles with the hostile nature as well as their kinship. Even though they are both outcast to the society – the brutal world they are flung into, they, with the thirst for staying alive, still accept, learn and evolve. The outcast, surprisingly, become the best adapter to the novel environment, and then the last survivor.